Analysis of death cases in Shenyang City, China, for immunization adverse event surveillance, 2009-2021 - Dongmei Gao; Guihua Dong; Lijun Zhu; Nina Jia; Baijun Sun (Taylor & Francis Group, 2023)
Through the Chinese National Immunization Adverse Event Surveillance System (CNAEFIS), we collected reports of Adverse Event Following Immunization (AEFI) deaths in Shenyang from 2009 to 2021 with the aim of analyzing AEFI-related deaths and assessing the safety of vaccination. From 2009 to 2021, a total of 12 AEFI-related deaths were reported in Shenyang City, and autopsies were performed in 6 deaths. According to the assessment of the Expert Committee on Investigation and Diagnosis of AEFI 3 (25.0%) deaths were classified as severe vaccine reactions, 9 (75.0%) deaths were classified as coincidental events, and there were no immunization errors or psychological reactions. The overall estimated AEFI-related mortality rate was 0.12 per 100,000 vaccination doses. Spearman's rank correlation analysis showed no correlation between AEFI, severe vaccine reactions, and suspected vaccination-related deaths. Coincidental events are the most common type of death following vaccination, meaning that the risk of death following immunization is low, and ongoing AEFI surveillance and scientific causality assessment are essential to ensure the vaccine confidence. Detailed pre-vaccination health status questioning is also key to avoiding and reducing adverse events.